Analisis Kebutuhan Multimedia Interaktif Game Berbasis Software Construct 2 Pada Materi Sistem Pencernaan - Dhia Awalia Putri; Sepita Ferazona; Nurkhairo Hidayati (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to identify the needs of teachers and students regarding the development of interactive multimedia games based on Construct 2 for the digestive system. This study applied a mixed methods approach with a sequential exploratory design. Qualitative data were obtained through structured interviews with 11th-grade biology teachers at SMAN 5 Pekanbaru, while quantitative data were collected through a needs analysis questionnaire administered to 30 students. The results showed that teachers have implemented the Independent Curriculum through the Project-Based Learning model, but still face limitations in utilizing interactive, game-based digital learning media. Meanwhile, students showed a high level of need for interactive multimedia games that are engaging, equipped with feedback features, and able to facilitate visualization of digestive system concepts in a more concrete and enjoyable way. These findings indicate that the development of interactive multimedia games based on Construct 2 software for the digestive system is urgently needed to increase learning engagement, conceptual understanding, and support meaningful learning in accordance with the demands of the Independent Curriculum.